Pedobarographic findings in patients with knee osteoarthritis - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2006)
Objective: The aim of this study was to evaluate pedobarographic findings and balance in knee osteoarthritis. Design: A total of 48 patients with knee osteoarthritis and 30 controls were included in this study. Pedobarographic measures were obtained from all patients and controls. Pain intensity of patients was measured using the Visual Analog Scale. The percentage of pressure on forefoot and hindfoot was measured using static pedobarography, and the peak pressures at forefoot, midfoot, and hindfoot were measured using dynamic pedobarography. The center-of-pressure sway length and width were measured for evaluation of balance. Results: The percentage of right hindfoot pressure (P < 0.05) and peak pressure of the right forefoot during walking were lower in the osteoarthritic group than in the controls (P < 0.05). The sway width in the patient group was higher than in the control group (P < 0.05). The Visual Analog Scale score at rest was negatively correlated with peak pressures of both right and left hindfeet in the osteoarthritic group (P < 0.05). The grade of osteoarthritis was positively correlated with sway length and sway width (P < 0.05). Conclusion: Pedobarography may become a useful technique to determine foot pressures that change because of disturbed weightbearing and balance problems in knee osteoarthritis.
Keywords: pedobarography; knee osteoarthritis; balance; peak pressure of foot; DEFORMITY; BALANCE; PAIN